NEW JOBS AND NEW SKILLS FOR A CHANGING WORKPLACE: STEM-Enabled Technicians and Professionals. - Malyn-Smith, Joyce; Smith, David M. (Career Planning & Adult Development Journal)
Chapter 3 of the Summer 2013 issue of the "Career Planning and Adult Development Journal" is presented. This chapter focuses on job skills needed to succeed in highly technical work environments. These include expert thinking, complex communication, computational thinking, intergenerational communication, navigating organizational cultures, collaborating face to face and in virtual environments, working in geographically distributed teams, and using social media to build business.